Crack Assessment on a Residential Building Due to Peat Soil Settlement at Ayer Hitam, Muar - Tuan Norhayati Tuan Chik; Nursyahirah Suhaimy; Nor Athirah Farhah Mat Jali; Nor Aiza Erme Mohamad (Journal of Structural Monitoring and Built Environment, 2024)
Frequent problems in structure that build on the peat soil is cracking. This is due to the settlement that occurred by the peat soil as it has low in bearing capacity. The crack occurred on the residential building have become the main concern as crack happened on building showed the earliest sign of degradation. The increasing number of visible cracks at residential building with varies in length and width has a doubtful taught either the residential building is safe or not to be used. Apart from cracking, the concrete strength of the residential building is a concerned as the crack occurred may reduce the concrete strength. A single-storey residential building at Kompleks Penghulu Mukim Ayer Hitam, Muar is used to perform field measurement with respect to the cracking and concrete strength. 25 number of visible cracks with different length and width has been detected while monitoring the building. The crack length and size were measured using ruler and measuring tape. For measuring the concrete strength, a non-destructive testing (NDT) was used using Schmidt Rebound Hammer and Ultrasonic Pulse Velocity (UPV). The total 15 point was tested on column and wall inside the residential house by using two modes of transmission for UPV testing which was semi-direct and indirect transmission. The result of both rebound number and UPV has been analyze using statistical evaluation. The result is then being compared with the previous researcher that using the same regression mode of linear and non-linear mode when doing the analysis. From the result, it is found that the regression model for rebound hammer is more reliable to be used as the regression coefficient value got is nearly to one. For overall cracking and concrete strength quality, it is also found that the residential building needs proper maintenance as the settlement still happened and it is affected the residential building’s safety.